Heterosis and Qualitative Attributes in Winter Tomato (Solanum lycopersicum L.) Hybrids (Bangladesh Journal of Agricultural Research, 2012)
An investigation was carried out at the Research Farm of Olericulture Division of Horticulture Research Centre of Bangladesh Agricultural Research Institute (BARI) to evaluate the heterotic performance in F1 generation of tomato. The hybrids showed significant variation in heterosis. The highest heterobeltiotic effects were observed in the cross P3 x P8 (-18.46%) for earliness, P1 x P6 (8.57 %) for flowers per cluster, P2 x P6 (21.73%) for fruits per cluster, P6 x P7 (75.54%) for plant height, P5 x P6 (67.44%) for fruits per plant, P9 x P10 (54.82 %) for yield per plant, P2 x P8 (21.21 %) for individual fruit weight, P7 x P8 (3.09 %) for fruit length, P3 x P8 (14.11 %) for fruit diameter and P1 x P6 (13.11 %) for brix content. In respect of fruit external characters like shape, pedicel area, shape of pistil scar, blossom end shape genotypes were found diverse. Internal qualitative character like firmness, fleshiness and less seeded and locule numbers were highly variable among the genotypes. Considering all the characters the crosses P1 x P8, P2 x P6, P2 x P7, P2 x P8, P3 x P8 and P5 x P6 were found suitable for further studies to variety selection. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11175 Bangladesh J. Agril. Res. 37(1): 39-48, March 2012